Hubungan antara Kecerdasan Emosional dengan Stres Akademik pada Mahasiswi yang Sedang Mengerjakan Skripsi di Universitas Negeri Padang - Septiani, Resti Ayu; Guspa, Anindra (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the relationship between emotional intelligence and academic stress among female students, particularly those completing their undergraduate thesis, despite the significant psychological and academic impact of this phenomenon. The purpose of this study is to examine the relationship between emotional intelligence and academic stress among female students at Universitas Negeri Padang who are in the process of writing their thesis. This research employs a quantitative correlational approach with purposive sampling, involving 410 female students as the sample. Data were collected through questionnaires distributed both online and offline, and analyzed using the product moment correlation technique. The results indicate a significant positive relationship between emotional intelligence and academic stress, suggesting that higher emotional intelligence is associated with higher levels of academic stress among female students. These findings support the theory proposed by Simbolon and Limbong (2022), and suggest that emotional intelligence does not always function as a protective factor against stress; rather, it may also intensify individuals’ perceptions of academic pressure. The main conclusion of the study is that the two variables are significantly and interdependently related. The implications include contributions to the literature on the psychological dynamics of final-year students, as well as practical recommendations for educational institutions to offer emotional intelligence training alongside stress management strategies. This study also opens avenues for further exploration among male student populations to achieve a more comprehensive understanding.